Towards a sustainable approach of energy policy in the EU: empirical evidence for Romania vs. the Visegrad Group based on the relationship among disruptive technology, knowledge and final energy consumption - Burciu, Aurel; Bostan, Ionel; Kicsi, Rozalia; Buta, Simona; Zoltan, Raluca; Condratov, Iulian (Frontiers in Energy Research, 2025)
This study aims to argue the role of disruptive technologies in reducing Final Energy Consumption (FEC) for 5 EU member states (Romania vs. the Visegrad Group), as well as the EU27 average for the period 2010–2020, in the context of current energy crisis, as a response to sustainable development imperatives. At the time of 2022, it proves once again that the state is needed to optimize the functioning of energy markets. From a theoretical perspective, the study brings two elements of absolute novelty. First, the study proposes a new model to determine two composite indexes related to the level of endowment with disruptive technologies (DEDT - Degree of Endowment for Disruptive Technologies) and the level of knowledge per capita (PCK - Per Capita Knowledge). The determination of DEDT and PCK was based on existing studies, statistical data as well as the authors’ consultation with a panel of experts in the use of digital technologies relevant to reducing FEC. Second, the study argues that even a relatively low annual increase in DEDT and knowledge of the EU-27 population is positively correlated with the reduction of FEC, the increase of GDP (Gross Domestic Product) and the shift of countries/firms towards the green economy and sustainable development. From a pragmatic perspective, the results of the study are of both direct and indirect interest for EU Member States’ policies, as well as for firms and families in their attempt to reduce FEC and to focus their behavior on the SDGs (Sustainable Development Goals).